Systematic evaluation of a panel of 30 synthetic cannabinoid receptor agonists structurally related to MMB‐4en‐PICA, MDMB‐4en‐PINACA, ADB‐4en‐PINACA, and MMB‐4CN‐BUTINACA using a combination of binding and different CB1 receptor activation assays: Part I—Synthesis, analytical characterization, and binding affinity for human CB1 receptors. Issue 7 (6th May 2021) - Pike, Edward; Grafinger, Katharina Elisabeth; Cannaert, Annelies; Ametovski, Adam; Luo, Jia Lin; Sparkes, Eric; Cairns, Elizabeth A.; Ellison, Ross; Gerona, Roy; Stove, Christophe P.; Auwärter, Volker; Banister, Samuel D.
Abstract: Synthetic cannabinoid receptor agonists (SCRAs) are one of the largest and most structurally diverse classes of new psychoactive substances (NPS). Despite this, pharmacological data are often lacking following the identification of a new SCRA in drug markets. In this first of a three‐part series, we describe the synthesis, analytical characterization, and binding affinity of a proactively generated, systematic library of 30 indole, indazole, and 7‐azaindole SCRAs related to MMB‐4en‐PICA, MDMB‐4en‐PINACA, ADB‐4en‐PINACA, and MMB‐4CN‐BUTINACA featuring a 4‐pentenyl (4en‐P), butyl (B/BUT), or 4‐cyanobutyl (4CN‐B/BUT) tail and a methyl l ‐valinate (MMB), methyl l ‐ tert ‐leucinate (MDMB), methyl l ‐phenylalaninate (MPP), l ‐valinamide (AB), l ‐ tert ‐leucinamide (ADB), l ‐phenylalaninamide (APP), adamantyl (A), or cumyl head group. Competitive radioligand binding assays demonstrated that the indazole core conferred the highest CB1 binding affinity ( K i  = 0.17–39 nM), followed by indole‐ ( K i  = 0.95–160 nM) and then 7‐azaindole‐derived SCRAs ( K i  = 5.4–271 nM). Variation of the head group had the greatest effect on binding, with tert ‐leucine amides and methyl esters ( K i  = 0.17–14 nM) generally showing the greatest affinities, followed by valine derivatives ( K i  = 0.72–180 nM), and then phenylalanine derivatives ( K i  = 2.5–271 nM). Adamantyl head groups ( K i  = 8.8–59 nM) were suboptimal for binding, whereas the cumyl analogues consistently conferred high affinity ( K i  = 0.62–36 nM). Finally, both butyl ( K i  = 3.1–163 nM) and 4‐cyanobutyl ( K i  = 5.5–44 nM) tail groups were less favorable for CB1 binding than their corresponding 4‐pentenyl counterparts ( K i  = 0.72–25 nM). Abstract : Synthesis, analytical characterization, and binding affinity of a systematic library of 30 indole, indazole, and 7‐azaindole SCRAs related to MMB‐4en‐PICA, MDMB‐4en‐PINACA, ADB‐4en‐PINACA, and MMB‐4CN‐BUTINACA featuring a 4‐pentenyl (4en‐P), butyl (B/BUT), or 4‐cyanobutyl (4CN‐B/BUT) tail and a methyl l ‐valinate (MMB), methyl l ‐ tert ‐leucinate (MDMB), methyl l ‐phenylalaninate (MPP), l ‐valinamide (AB), l ‐ tert ‐leucinamide (ADB), l ‐phenylalaninamide (APP), adamantyl (A), or cumyl head group.